2001
DOI: 10.1128/cdli.8.4.695-701.2001
|View full text |Cite
|
Sign up to set email alerts
|

Induction by a Lactic Acid Bacterium of a Population of CD4+T Cells with Low Proliferative Capacity That Produce Transforming Growth Factor β and Interleukin-10

Abstract: We investigated whether certain strains of lactic acid bacteria (LAB) could antagonize specific T-helper functions in vitro and thus have the potential to prevent inflammatory intestinal immunopathologies. All strains tested induced various levels of both interleukin-12 (IL-12) and IL-10 in murine splenocytes. In particular, Lactobacillus paracasei (strain NCC2461) induced the highest levels of these cytokines. Since IL-12 and IL-10 have the potential to induce and suppress Th1 functions, respectively, we addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(125 citation statements)
references
References 49 publications
(56 reference statements)
4
118
0
1
Order By: Relevance
“…In rats with induced enterocolitis, the concentration of CD4 + and CD8 + cells in the intestinal lamina propria were increased to a more normal level by administration of L. plantarum (Mao et al, 1996). In another study, L. paracasei NCC2461 induced the development of a population of CD4 + T-cells with low proliferative capacity and that were induced to produce transforming growth factor (TGF)-b and interleukin (IL)-10 (von der Weid et al, 2001). In the current study, treatment with AFM 1 + L. rhamnosus GAF01 (at 1 g/kg BW) resulted in a significant improvement in immune system cell total counts (towards control levels), although in the end they were still different than control values.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with induced enterocolitis, the concentration of CD4 + and CD8 + cells in the intestinal lamina propria were increased to a more normal level by administration of L. plantarum (Mao et al, 1996). In another study, L. paracasei NCC2461 induced the development of a population of CD4 + T-cells with low proliferative capacity and that were induced to produce transforming growth factor (TGF)-b and interleukin (IL)-10 (von der Weid et al, 2001). In the current study, treatment with AFM 1 + L. rhamnosus GAF01 (at 1 g/kg BW) resulted in a significant improvement in immune system cell total counts (towards control levels), although in the end they were still different than control values.…”
Section: Discussionmentioning
confidence: 99%
“…An overall trend for an increase in serum sCD14 concentrations during the first year of life, which reached statistical significance at 12 mo of age was observed. Stimulation of CD14 and TLR2 by microbial products has been demonstrated to induce TGF-␤ production in human colonic cell lines (28) and probiotic strains of lactobacilli have been reported to induce the development of T cells producing TGF-␤ in vitro (29). In addition, there are data to suggest that CD14 is required for lactobacilli to induce a response (30).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 might also have an indirect anti-inflammatory effect because it also stimulates together with TGF-␤ IgA synthesis (40). The probiotic Lactobacillus paracasei has been shown to maintain IL-10 and induce TGF-␤ secretion by CD4ϩ T cells (41). An in vitro study has demonstrated that the incubation of the probiotic L. plantarum with mononuclear cells isolated from actively inflamed colon results in a significant increase of IL-10 (42).…”
Section: Discussionmentioning
confidence: 99%